Striking a balance : complexity and knowledge landscapes / David Oliver and Johan Roos. - Oliver, David, 1951- (McGraw-Hill, 2000)
This text is designed to help managers respond better to today's complex business environment by balancing the need to adapt to new requirements in their competitive environments while seizing new opportunities to shape these environments.